2013
DOI: 10.1590/s0103-507x2013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Dosagens séricas de proteína C-reativa na fase inicial da sepse abdominal e pulmonar

Abstract: ObjectivesTo evaluate the C-reactive protein serum levels in patients with pulmonary and abdominal sepsis during the first five days of sepsis progression. Methods The present investigation was a retrospective cohort study conducted at the university hospital with 345 patients who were admitted to the intensive care unit and diagnosed with sepsis of pulmonary or abdominal origin. Serum C-reactive protein concentrations were measured by the turbidimetric immunoassay. For analysis of C-reactive protein, day 1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 20 Numerous studies have reported the high sensitivity and specificity of CRP for the diagnosis of sepsis. 21 23 In ICU patients, elevated concentrations of serum CRP upon admission are correlated with an increased risk of organ failure and death. 24 However, other studies have demonstrated that CRP levels are not indicative of survival in sepsis patients.…”
Section: Proinflammatory Biomarkersmentioning
confidence: 99%
“… 20 Numerous studies have reported the high sensitivity and specificity of CRP for the diagnosis of sepsis. 21 23 In ICU patients, elevated concentrations of serum CRP upon admission are correlated with an increased risk of organ failure and death. 24 However, other studies have demonstrated that CRP levels are not indicative of survival in sepsis patients.…”
Section: Proinflammatory Biomarkersmentioning
confidence: 99%
“… 33 Patients with abdominal sepsis had higher CRP than those with pulmonary sepsis (mean 178 versus 149 mg/L) (Brazil). 34 …”
Section: Resultsmentioning
confidence: 99%
“…The role of conventional inflammatory biomarkers (CRP and PCT) in the diagnosis of sepsis/septic shock and the prediction of prognosis is controversial [ 16 , 17 , 18 , 19 , 20 ]. Also, these biomarkers are mostly increased in severe bacterial infections, but their late rise, elevation during some viral infections, and the requirement for serial measurement limit their use in the ED for the differential diagnosis and prognosis of sepsis and septic shock [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%